Geochemical Records of the Provenance and Silicate Weathering/Erosion From the Eastern Arabian Sea and Their Responses to the Indian Summer Monsoon Since the Mid‐Pleistocene. Issue 4 (28th March 2020) - Chen, Hongjin; Xu, Zhaokai; Lim, Dhongil; Clift, Peter D.; Chang, Fengming; Li, Tiegang; Cai, Mingjiang; Wang, Wei; Yu, Zhaojie; Sun, Rongtao
Abstract: We present a multiproxy record of Sr‐Nd isotopes and major and trace elements for clay‐sized (<2 μm) siliciclastic sediment fractions from the International Ocean Discovery Program Site U1456 in the eastern Arabian Sea to extract reliable chemical indicators not influenced by the grain‐size effect, quantitatively estimate detrital provenance, and constrain silicate weathering/erosion in response to the Indian summer monsoon over orbital timescales. A provenance analysis of fine‐grained siliciclastic sediments indicates a two end‐member mixture from the Indus River (20–90%) and rivers draining the Deccan Traps (10–80%). A prominent increase in terrigenous input from the Indus River occurred at ~0.5 Ma, probably resulting from an intensive erosional event in the Himalayan region. Moreover, α Al K at Site U1456, which is calculated as Al/K ratio of the study sample versus Al/K ratio of the upper continental crust, can be generally used to reflect the chemical weathering intensity in the source regions. During most interglacial and even certain glacial periods, the Indian summer monsoon reinforcement is closely coupled with enhanced continental chemical weathering and physical erosion. Wavelet and spectral analyses of the α Al K record display strong 125‐, 35‐, 29‐, and 23‐kyr periodicities since 1.2 Ma with significant ~100‐kyr cycles established at the end of the Mid‐Pleistocene Transition (~0.7 Ma), suggesting forcing mechanisms linked with both Northern and Southern Hemispheric processes. Significant fluctuations observed in silicate weathering/erosion during ~1.2–0.7 Ma indicate an enhancement of the Indian summer monsoon with increased variability in association with the Mid‐Pleistocene Transition. Key Points: Indus River and Deccan Traps supplied fine‐grained sediments to the eastern Arabian Sea since 1.2 Ma The Indian summer monsoon reinforcement can trigger strong chemical weathering and rapid continental erosion over orbital timescales α Al K records indicate significant changes in the Indian summer monsoon in association with the Mid‐Pleistocene Transition